A Family Cluster of Coronavirus Disease (COVID-19) Infection with Different Clinical Manifestations - Soedarsono Soedarsono (Interna Publishing, 2020)
Coronavirus disease 2019 (COVID-19) caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) had been declared as a global pandemic by WHO. During the pandemic, a suspicion of COVID-19 infection could be found on patients presented with clinical symptoms of COVID-19. However, several new clinical symptoms of COVID-19 had also been reported recently. This caused difficulties to identify COVID-19 based on the clinical symptoms only. Real-Time Reverse Transcriptase-Polymerase Chain Reaction (RT-PCR) was absolutely needed to determine the correct diagnosis. We report a family cluster of COVID-19 with different clinical manifestations to show a potential COVID-19 transmission in person who has no symptoms initially but may develop symptoms later as the incubation period varies from 5-14 days. This asymptomatic person remains potential to transmit the virus. This report describes the epidemiological, clinical, radiological, laboratory findings, and different clinical manifestation of a family cluster of COVID-19 case in Indonesia. COVID-19 was transmitted from asymptomatic person in the incubation period.